2017
DOI: 10.1186/s13617-017-0055-8
|View full text |Cite
|
Sign up to set email alerts
|

Household preparedness motivation in lahar hazard zones: assessing the adoption of preparedness behaviors among laypeople and response professionals in communities downstream from Mount Baker and Glacier Peak (USA) volcanoes

Abstract: As the number of people living at risk from volcanic hazards in the U.S. Pacific Northwest grows, more detailed studies of household preparedness in at-risk communities are needed to develop effective mitigation, response, and recovery plans. This study examines two aspects of preparedness behavior motivation in the Skagit Valley (WA), which is at risk from Mount Baker and Glacier Peak lahars. First, we examine the influence of perceived responseefficacy, protective response costs, self-efficacy, and ascriptio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 34 publications
1
13
0
Order By: Relevance
“…The relevant emergency items were prioritised in accordance with the National Disaster Prevention Manual published by the Ministry of Civil Affairs of China and the CDC Behavioral Risk Factor Surveillance System. These included nine general emergency necessities (3-day supply of non-perishable food and water, battery-powered radio, extra batteries, battery-operated torch, first-aid kit, gas mask, fire extinguisher, escape ropes, whistle) as recommended by the national public education ‘ready’ programme in the USA and some preparedness items source from the General Preparedness Module,18 19 as well as coverage of accident insurance, knowledge of local emergency response systems (emergency numbers, exit routes and shelters) and availability of an evacuation plan 20 21…”
Section: Methodsmentioning
confidence: 99%
“…The relevant emergency items were prioritised in accordance with the National Disaster Prevention Manual published by the Ministry of Civil Affairs of China and the CDC Behavioral Risk Factor Surveillance System. These included nine general emergency necessities (3-day supply of non-perishable food and water, battery-powered radio, extra batteries, battery-operated torch, first-aid kit, gas mask, fire extinguisher, escape ropes, whistle) as recommended by the national public education ‘ready’ programme in the USA and some preparedness items source from the General Preparedness Module,18 19 as well as coverage of accident insurance, knowledge of local emergency response systems (emergency numbers, exit routes and shelters) and availability of an evacuation plan 20 21…”
Section: Methodsmentioning
confidence: 99%
“…The limited and inconsistent role of responsibility attribution in natural hazards risk perception and the adoption of protective behaviors highlighted the need for more studies (Corwin et al, 2017). Therefore, we hypothesize that: Compared with the ones feeling more personal responsibility, the ones feeling more government responsibility would have H3a lower degrees of perceived probability, H3b a lower degree of perceived consequence, and H3c a lower degree of worriment for both typhoon and earthquake disasters .…”
Section: Literature Reviewmentioning
confidence: 99%
“…Other researchers, such as Baker et al ( 20), Murti et al, and Corwin et al (6,21), have emphasized all or some of these categories. The results of this study demonstrated that in order to increase the physical-operational preparedness of families, structural and non-structural safety measures should be taken in the house; moreover, a disaster supplies kit should be prepared and its contents should be checked periodically.…”
Section: Discussionmentioning
confidence: 99%
“…In agreement with other studies, the acquisition of first aid skills was another sub-component identified in physical-operational preparedness in this study. Ejeta et al and Corwin et al emphasized the importance of learning first aid (26,21).…”
Section: Discussionmentioning
confidence: 99%